Robotic-assisted surgery and kinematic alignment in total knee arthroplasty (RASKAL study): a protocol of a national registry-nested, multicentre, 2×2 factorial randomised trial assessing clinical, intraoperative, functional, radiographic and survivorship outcomes. Issue 6 (10th June 2022) - MacDessi, Samuel J; Wernecke, Gregory C; Bastiras, Durga; Hooper, Tamara; Heath, Emma; Lorimer, Michelle; Harris, Ian
Abstract : Introduction: Robot-assisted surgery (RAS) and kinematic alignment (KA) are being increasingly adopted to improve patient outcomes in total knee arthroplasty (TKA). There is uncertainty around the individual or combined effect of these concepts compared with computer-assisted surgery (CAS) and mechanical alignment (MA), respectively. This study aims to assess the effectiveness of RAS, KA or both to improve clinical outcomes, functional measures, radiographic precision and prosthetic survivorship when compared with current gold standards of surgical care. Methods and analysis: A national registry-nested, multicentre, double-blinded, 2×2 factorial, randomised trial will be undertaken with 300 patients undergoing primary unilateral TKA performed by 15 surgeons. The primary outcome will be the between-group differences in postoperative change over 2 years in the mean Knee injury and Osteoarthritis Outcome Score (KOOS-12), comparing first, RAS to CAS as its control, and second, KA to MA as its control. Secondary outcomes will include other knee-specific and general health patient-reported outcome measures (PROMs), intraoperative pressure loads as a measure of soft tissue balance, 6-month postoperative functional outcomes, radiological precision using CT imaging, complications and long-term prosthetic survivorship. The contribution of each patient's unique coronal plane alignment of the knee phenotype to primary and secondary PROMs will be investigated. OMERACT-OARSI criteria and Patient Acceptable Symptom State outcome score thresholds for the KOOS-12 and Oxford Knee Score will be used in secondary analyses. Primary intention-to-treat and secondary per-protocol analyses will be performed. Statistical analysis will include a generalised linear mixed model for repeated measures for continuous KOOS-12 scores. Kaplan-Meier estimates with adjusted HRs of implant survivorship will be calculated. Ethics and dissemination: Ethics approval was obtained from Sydney Local Health District-Royal Prince Alfred Hospital (Approval X20-0494 and 2020/ETH02896 10.24/DEC20). Results will be submitted for publication in a peer-reviewed journal and presented in national, state and international meetings. Trial registration number: ACTRN12621000205831.